Kedalaman Jiwa: Perspektif Alkitab Tentang Hakekat Manusia - Aben Tuke Banamtuan; Aprianus Lendrik Moimau (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
In a Biblical perspective, human nature is understood as a creature created by God that is unique and different from other creations of God. Humans are unique in intellectual, social, physical and spiritual terms, which contain responsibilities towards themselves, others, nature andto God.Humans consist of body, soul and spirit, each of which has an important role in human life. .the body reveals the human person in its entirety from an outward aspect, while the soul or life reveals the whole person from an inner aspect, as a creature that breathes, wills, thinks, and so on. The spirit is the aspect of human life with an inner mind too, which can receive andexpress spiritual observations.